The book of wanderers - Ramirez, Reyes, 1989- (Camino del sol., 2022)
"The Book of Wanderers is a collection of short stories that explores Latinx identity through the lens of newer generations of Mexican and Salvadoran diasporas to the US. The theme of wandering comes up in each story, whether it be through feelings of unease or liberation, especially due to the cultural, physical, and/or psychological separation or loss from one generation to the next as a result of living in a tumultuous nation. To capture the complexity of Latinx identity, the stories also play with and within different genres, from 'literary' realist fiction to hallucinatory realist, magical realist, noir, science fiction, and speculative fiction stories"--